Potential Nephrotoxic Effect of UV-328 and Its Possible Salvage by Dimethoxy Curcumin in Zebrafish - Senthilmurugan, S.; Prinitha , R.; Vijayan , P.; Miltonprabu, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The occurrence of Benzotriazole UV Stabilizer-328 (UV-328) in different environmental and natural systems is of fast regular concern these days. In this current paper, we assessed the renotoxicity of UV-328 in zebrafish kidney tissues to know the chore of oxidative devilry in kidney and to recuperate the renotoxicity utilizing Dimethoxy curcumin (DiMC) supplementation. Grown-up zebrafish were exposed 55µg/L of UV-328 and DiMC supplemented through diet at 50mg/kg BW. Close to the completion of 28 days, renal tissues were examined for the responses of oxidative pressure, antioxidant status and histopathological changes. The results demonstrated that antioxidant enzymes such as, Glutathione (GSH) levels and the activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione-S-transferase (GST) were all reduced in zebra fish kidneys treated with UV-328. Renal malondialdehyde (MDA) levels was brought prominently up in the UV-328 treated fish. All of the altered variables significantly returned to near-normal levels in the DiMC-supplemented group. Histopathological lesions, viz., hypertrophied glomerulus, cytoplasmic and nuclear degeneration, cytoplasmic vacuolization, degeneration of renal tubules were seen in UV-328 treated kidney of zebrafish which were actually reinforced in the DiMC treated fish. From our outcomes, it has been proposed that even at the low-level convergence of UV-328 exposure is malicious and to provoke oxidative insult, cell reinforcement exhaustion and kidney neurotic devilry in zebrafish and remediation with DiMC has been ended up being the better choice to conquer the harmful oppression prompted by UV-328.